Assessment of the engineering properties of biomass recycled aggregate concrete developed from coconut shells. (1st August 2022) - Liu, Haibao; Li, Qiuyi; Ni, Songyuan
Highlights: Biomass recycled aggregates such as CCSA and SBRA were prepared using coconut shells. The wrapping treatment can effectively improve the properties of biomass aggregates. Reduction of water-cement ratio and carbonation of aggregates can improve the performance of biomass-aggregate concrete. Abstract: This study examines the potential of using biomass recycled aggregates developed from coconut shells to replace aggregates in structural concrete. Compared with natural aggregate (NA), coconut shell has many disadvantages as coarse aggregate in concrete due to the differences in structure, particle shape, and density from NA. Therefore, the contribution of this study is to improve the possibility of using agricultural byproducts in structural concrete. The main experimental work is to clarify the effect of using crushed coconut shell aggregate (CCSA) and synthetic biomass recycled aggregate (SBRA), which are developed based on coconut shell, to replace NA with comparable mechanical properties, shrinkage properties, thermal conductivity, microstructure of concrete. The results indicated that the mechanical strength of concrete with SBRA in 3d and 28d achieved at least 90 % and 80 % strength of that of natural aggregate concrete (NAC), respectively. In addition, compared with NAC, crushed coconut shell aggregate concrete (CCSAC) and synthetic biomass recycled aggregate concrete (SBRAC) show significant improvements in thermal conductivity, showing excellent building energy saving potential. Compared with CCSA, the cement paste matrix surrounding the SBRA can effectively prevent water loss and reduce the thickness of interfacial transition zone (ITZ) to less than 10 mm, thus ensuring the volume stability of concrete; The lower water-cement ratio and carbonized SBRA (C-SBRA) had positive effects on improving the properties of CCSAC and SBRAC, respectively.